Controlling and visualizing fracture of 2D crystals by wrinkling. (May 2023) - Feng, Shizhe; Wang, Wenxiang; Wang, Shijun; Cui, Xuwei; Yang, Yifan; Xu, Fan; Liu, Luqi; Xu, Zhiping
Abstract: Shaping two-dimensional (2D) crystals with well-defined edges along specific directions remains technically challenging due to the intrinsic lattice discreteness and anisotropy in their fracture toughness. The patterns of crystal cleavage are determined by the fracture resistance and loading conditions, and usually display kinking features. We show that the fracture of single-crystalline 2D films (MoS2, MoTe2, graphene) can be controlled by mechanically-induced wrinkles, and the distortion of their profiles can visualize the distorted local strain state near the crack tip. In thin samples with stretch-induced wrinkles, the elastic driving force with effective anisotropy steers crack propagation, resulting in straight edges following the corrugation profile. In contrast, thick samples remain flat under stretch for their elevated bending resistance, and the cracks advance with sawtooth patterns following the zigzag motif. The experimental findings are explained by wrinkling-induced elastic anisotropy, which dominates over fracture anisotropy. The control of fracture in 2D crystals can be applied to fabricate micro- and nanostructures for their applications in electromechanical and optoelectronic devices. Highlights: Unveiling the role of wrinkling in selecting crack directions in 2D crystals. Establishing the theory of crack propagation with anisotropy in effective elasticity and fracture toughness. Demonstrating a procedure to control the fracture of 2D crystals and visualize the crack tip strain field.